2007
DOI: 10.1096/fj.06-6408com
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress increases myofiber formationin vitro

Abstract: Myoblast differentiation involves myoblast fusion followed by myofiber formation. We recently demonstrated that endoplasmic reticulum (ER) stress signaling occurs during myoblast differentiation in vivo. This signaling results in apoptosis in a subpopulation of myoblasts. In a cell culture model of myogenesis, inhibition of ER stress signaling blocked apoptosis and myoblast differentiation. To further examine the role of ER stress during myogenesis, we exposed cultured myoblasts to ER stress inducers during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
109
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 43 publications
6
109
0
2
Order By: Relevance
“…By contrast, the processing of other known apoptotic initiator caspases, caspase-1, caspase-2 and caspase-8, was not detectable. We have not excluded a role for the other mouse initiator, caspase-12, which might have importance in this process, given the effect of endoplasmic reticulum (ER) stress on myoblast differentiation (Nakanishi et al, 2007). Second, the processing of caspase-9 suggests autocatalytic proteolysis, consistent with caspase-9 being the initiator.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, the processing of other known apoptotic initiator caspases, caspase-1, caspase-2 and caspase-8, was not detectable. We have not excluded a role for the other mouse initiator, caspase-12, which might have importance in this process, given the effect of endoplasmic reticulum (ER) stress on myoblast differentiation (Nakanishi et al, 2007). Second, the processing of caspase-9 suggests autocatalytic proteolysis, consistent with caspase-9 being the initiator.…”
Section: Discussionmentioning
confidence: 97%
“…However, active caspase-12 is also present in nonapoptotic myogenic cells during development, indicating that it has additional functions beyond initiating apoptosis (56). Several studies suggest a role for caspase-12, -9 and -3 in promoting myoblast differentiation (52,53,55). In contrast, Moresi et al (54) found that increased caspase activity delayed muscle regeneration, by a mechanism independent of caspase-3 and apoptosis, while caspase inhibition improved muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31] In particular, during myogenesis ER stress enhances myoblast differentiation and myofiber formation. 32 Cho et al 31 have shown that ER stress increases during ESC differentiation toward neural cells and that this differentiation is further enhanced through chemical treatment with the ER stress inducers, thapsigargin and tunicamycin. We demonstrated that Nrf3 localizes to the ER at different stages of differentiation ( Figure 6A) and Zhang et al 26 have demonstrated that ER chemical stressors in COS-1 cells activate Nrf3.…”
Section: Discussionmentioning
confidence: 99%